Factors Associated with Foot Ulcer among Diabetic Patients - Theodehild M. Theresia Dee; Tintin Sukartini; Ririn Probowati (Alta Dharma Publisher, 2020)
Diabetic foot ulcers (DFU) are among the most common complications in diabetic patients and are associated with high morbidity, mortality, and health costs. Peripheral neuropathy, peripheral arterial disease, and foot deformity are risk factors for diabetic foot ulcers. Identification of risk factors is needed to improve diabetic foot ulcer prevention strategies. This study aimed to describe the results of the monofilament 10 g test and ankle-brachial index in patients with diabetes mellitus. In this cross-sectional study, a total of 70 patients with diabetes mellitus type 1 and type 2 were included. The sampling technique used was purposive sampling. The results showed 54.3% of respondents had peripheral neuropathy with a monofilament score ? 8. There were 27.1% of respondents with a lower score in ABI ? 0.9 and indicated peripheral arterial disease. The monofilament test with a score of ? 8 was more common in women than in men, ages 56-65 years, and duration of diabetes mellitus for more than ten years. A lower ABI was more common in women than in men, aged 56-65 years, and duration of diabetes mellitus for more than ten years. Peripheral neuropathy and peripheral arterial disease are risk factors for diabetic foot ulcers. Therefore prevention and early screening are needed